La “letteratura dal basso”. Il caso di Alberto Manzi, maestro scrittore - Chiara Lepri (Studi sulla Formazione, 2025)
Starting from the early 1950s, a literary trend developed in conjunction with the first attempts to renew teaching models, promoted above all by the MCE, which involved some teachers as authors, mostly elementary school teachers, who became witnesses of the narrative experiences of children and young people directly involved in the development of stories within school structures. These were often experiences conducted in marginal places during the years of post-war reconstruction, where the school became an outpost in the process of emancipation and democratization of the masses starting from the social practices that took place in the classroom. Alberto Manzi was among the first to conduct a collective writing experiment in the classroom; there were then numerous militant teachers who chose, in difficult and deprived contexts, to favor the path of storytelling and dialogue to start a process of knowledge and literacy that was not only instrumental, but also civil and imaginary. In the happiest cases, a children’s literature is born that develops “from below” and that is able to intersect the experiential and inventive paths of the recipients while at the same time ensuring high aesthetic standards, since the texts produced do not operate towards a “child-friendly” simplification, but rather towards the elevation of a literary expression capable of effectively intercepting reality and giving rise to creative representation.